2015
DOI: 10.1631/jzus.b1500013
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation and acetogen population changes in response to an exogenous acetogen TWA4 strain and Saccharomyces cerevisiae fermentation product

Abstract: Abstract:The presence of yeast cells could stimulate hydrogen utilization of acetogens and enhance acetogenesis. To understand the roles of acetogens in rumen fermentation, an in vitro rumen fermentation experiment was conducted with addition of acetogen strain (TWA4) and/or Saccharomyces cerevisiae fermentation product (XP). A 2×2 factorial design with two levels of TWA4 (0 or 2×10 7 cells/ml) and XP (0 or 2 g/L) was performed. Volatile fatty acids (VFAs) were increased (P<0.05) in XP and TWA4XP, while methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…LA-supplemented and control groups in the study by Dohme et al (2001) had comparable concentrations during rumen fermentation using the rumen simulation technique. In addition, VFA concentrations were not affected by exogenous acetogens (Yang et al, 2015) or by 6 reductive acetogenic bacteria from a variety of ruminal and nonruminal environments (Lopez et al, 1999) when added in in vitro rumen fermentation, which corroborates the findings of this study when acetogen was independently provided to the animals. Meanwhile, the H-NMR spectroscopy results revealed no significant difference among treatments and no correlation between the LA and Con groups.…”
Section: Discussionsupporting
confidence: 85%
“…LA-supplemented and control groups in the study by Dohme et al (2001) had comparable concentrations during rumen fermentation using the rumen simulation technique. In addition, VFA concentrations were not affected by exogenous acetogens (Yang et al, 2015) or by 6 reductive acetogenic bacteria from a variety of ruminal and nonruminal environments (Lopez et al, 1999) when added in in vitro rumen fermentation, which corroborates the findings of this study when acetogen was independently provided to the animals. Meanwhile, the H-NMR spectroscopy results revealed no significant difference among treatments and no correlation between the LA and Con groups.…”
Section: Discussionsupporting
confidence: 85%
“…The species Acetitomaculum ruminis was only observed (RA >3%) in the manure-supplemented reactors C3-K1/2 and C4-VS1/2. It is a known acetogen present in the rumen and performs reductive acetogenesis (Greening and Leedle, 1989; Le Van et al, 1998;Yang et al, 2015). An increase in RA of this species and decrease in RA of Cloacimonetes_HGW3 was observed prior to VFA accumulation (~day 175-217) in reactor C4-VS2, indicating a role in acetogenesis and syntrophic acid oxidation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae fermentation products (SCFP) have also been evaluated for use as feed additives in dairy and beef production. Some studies have shown that SCFP can positively impact gastrointestinal health for cattle exposed to high-concentrate diets, by providing components including amino acids, peptides, organic acids, and oligosaccharides 1820 . In some studies, inclusion of SCFP in cattle diets improved performance characteristics, including increased milk production 21 , increased volatile fatty acid concentration, decreased rumen pH 22 , efficient feed conversion, and improved carcass traits 23 .…”
Section: Introductionmentioning
confidence: 99%